2018
DOI: 10.1111/joca.12207
|View full text |Cite
|
Sign up to set email alerts
|

“Four Bright Coins Shining at Me”: Financial Education in Childhood, Financial Confidence in Adulthood

Abstract: We show that receiving an allowance (pocket money) between age 8 and 12 increases financial confidence in adulthood. We measure the level of confidence using the self-reported financial knowledge. We carry out the analysis by using a Dutch survey conducted in 2015. We estimate causal effects by controlling for parental attitudes and using a "within family" fixed effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 63 publications
(70 reference statements)
0
20
0
1
Order By: Relevance
“…This study is crucial in the domain of the financial well‐being of young adults (Brüggen et al, 2017; Drever et al, 2015; Gutter & Copur, 2011; Marchant & Harrison, 2019; Norvilitis & MacLean, 2010; Sansone, Rossi & Fornero, 2018; Shim et al, 2009). Because a substantial number of students report low financial well‐being, educational institutions, financial institutions and policymakers must increasingly focus on young adults.…”
Section: Introductionmentioning
confidence: 99%
“…This study is crucial in the domain of the financial well‐being of young adults (Brüggen et al, 2017; Drever et al, 2015; Gutter & Copur, 2011; Marchant & Harrison, 2019; Norvilitis & MacLean, 2010; Sansone, Rossi & Fornero, 2018; Shim et al, 2009). Because a substantial number of students report low financial well‐being, educational institutions, financial institutions and policymakers must increasingly focus on young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that individuals start acquiring financial literacy at an early age (i.e., at childhood) within a financial socialisation process [26,[28][29][30][31], with a special role in the process played by parents [26]. Therefore, we expected that, generally, individuals more exposed to parental financial socialisation should report higher financial learning outcomes, that is, debt knowledge levels, debt skills levels, and financial confidence (i.e., subjective debt knowledge).…”
Section: Previous Empirical Evidence On Indirect Effectsmentioning
confidence: 96%
“…Financial literacy is considered a prerequisite for citizens' economic security [27]. On the other hand, some studies have shown that financial literacy is modelled during childhood within a financial socialisation process [26,[28][29][30][31], with a special role played by parents [26]. Hence, in light of the empirical research carried out so far, a hierarchical process seems to exist, leading from childhood experiences through adulthood financial literacy levels and financial behaviours to satisfaction and well-being states.…”
Section: Introductionmentioning
confidence: 99%
“…1 From a paediatric-research viewpoint, pocket-money is considered a minor variable to be assessed when examining the broader picture of children's negative health habits.…”
Section: Gp169 the Pocket-money Studymentioning
confidence: 99%